Ultrahigh electro-strain in acceptor-doped KNN lead-free piezoelectric ceramics via defect engineering - Zhao, Zhihao; Lv, Yukai; Dai, Yejing; Zhang, Shujun (Acta materialia, 2020)
Defect dipoles in acceptor-doped perovskite-based ferroelectric ceramics play an important role in piezoelectric properties. In this work, the acceptor, such as Fe2+ and Cu+, -doped (K0.5N0.5)NbO3 (KNN) ceramics are fabricated in reduced atmosphere by the conventional solid-state reaction method. By tailoring the strongly polarized defect dipoles through poling and aging processes, ultrahigh electro-strain and large signal piezoelectric d33* values can be achieved. The electro-strains of 0.41% and 0.50% with d33* ~820 pm/V and ~1000 pm/V are obtained in Fe2+-doped and Cu+-doped KNN samples, respectively, which are 4-fold and 5-fold larger than that of pure KNN. Of particular interest is that the electro-strain and d33* values are found to improve with increasing temperature up to 140°C, accompanied with low strain hysteresis of 10%-20%. A detailed mechanism considering the interaction between defect dipole polarization and spontaneous polarization after poling and aging processes is proposed to explain the observed phenomena, which provides a good paradigm for achieving high piezoelectric response by defect engineering in perovskite-based ferroelectric ceramics. [Display omitted]